Impact Of Abattoir Waste On The Physico-Chemical Quality Of Anwai River, Asaba Delta State, Nigeria - Ezemonye, Mary N.; Osiatuma, Stephanie I.; Emeribe, Chukwudi N. (European Scientific Journal, ESJ, 2016)
Abattoir management is left in the hands of the populace and to this end, the wastes generated thereof are handled without consideration of the impacts on the environment. The study established quality deterioration for rainy/dry season physicochemical parameters at downstream (points after the abattoir) as theyexceeded values of the control point (sample site before the abattoir). The analysis of variance test at 0.05 confidence level supports the fact that quality of Anwai River at effluent discharge point differ significantly from quality at control point during rainy season. The rainy season values of the physicochemical parameters for slaughter days far exceeded the non slaughter days. The ANOVA test to determine if dry season quality of the Anwai River at effluent discharge point differ significantly from quality at control point showed no statistical variation at 0.05 level of confidence of confidence suggesting reduced diffused pollution and transportation of pollutant during the dry season. The study also established that the season of the year does have effect on quality deterioration of Anwai River. Diffuse pollution was established to on Anwai River as a result of poor abattoir waste management. It is recommended that the State government intervenes to stem the indiscriminate disposal of abattoir waste into the river to help preserve the health of the river and Anwai community.